(untitled) (Research, Society and Development, 2022)
The understanding of professionals about the importance of vaccination is extremely important, since it is the health professional’s duty to provide guidance, and it is essential to have a good understanding of vaccination. Objective: To understand the vision and knowledge of undergraduate health students regarding the use of immunobiological. Methods: This is a descriptive survey, with quantitative analysis, conducted in a nursing, medicine and psychology college in the interior of São Paulo, with 103 nursing and medical students, from October to November 2021, using the Google Forms platform. Results: Most students were in their third year of undergraduate study (50.5%), followed by the fourth year (21.4%). Regarding the content of vaccination being covered in the undergraduate course, 72.8% (75) responded positively, with this content being addressed predominantly in the discipline of Health Surveillance (34.42%), also highlighting the disciplines of Immunology (19.67%) and Child and Adolescent Health (19.67%). Moreover, most students, 58.3% (60), did not participate in any course or event focused on the theme. In the analysis of the students’ performance, most students presented a very satisfactory (45.63%) or satisfactory (52.42%) performance, with only a minority being unsatisfactory (1.94%). It can be seen that the percentage of correct answers increased throughout the undergraduate course. Conclusion: This study concludes that undergraduate nursing and medical students had satisfactory knowledge about the subject and that this knowledge is progressive over the years.